Lessons for the UK Green Deal from the US BBNP. Issue 4 (19th May 2017) - Gillich, Aaron; Sunikka-Blank, Minna; Ford, Andy
ABSTRACT: How can programme design and strategy drive the decision actually to undertake retrofit upgrades? The US Better Buildings Neighborhood Program (BBNP) and the UK Green Deal both represent ambitious efforts to drive domestic retrofit markets. These programmes are compared and the differences in their conversion rates explored in the context of marketing, outreach and workforce engagement strategies. The impact of financial incentives is also explored. This paper supports the consensus that the US BBNP was successful against most of its stated objectives. The UK Green Deal, while slow to start, was gaining momentum before it was effectively ended. Semi-structured interviews with programme organizers give evidence that the Green Deal would have benefited from a more active approach to marketing and outreach, specifically emphasizing the distinction between the two. Marketing generates interest, but local outreach through word of mouth and personal referrals is needed to drive upgrades. The Green Deal did not sufficiently engage the workforce through an ongoing communication strategy and should have better facilitated both technical and non-technical skills development. The interest rate of the Green Deal is shown to be but one factor influencing participation, and can be effectively balanced through programme design in other areas.